Cytotoxicity and Initial Biocompatibility of Endodontic Biomaterials (MTA and Biodentine™) Used as Root-End Filling Materials. (9th August 2016) - Escobar-García, Diana María; Aguirre-López, Eva; Méndez-González, Verónica; Pozos-Guillén, Amaury
Abstract : Objective . The aim of this study was to evaluate the cytotoxicity and cellular adhesion of Mineral Trioxide Aggregate (MTA) and Biodentine (BD) on periodontal ligament fibroblasts (PDL). Methods . PDL cells were obtained from nonerupted third molars and cultured; MTS cellular profusion test was carried out in two groups: MTA and BD, with respective controls at different time periods. Also, the LIVE/DEAD assay was performed at 24 h. For evaluation of cellular adhesion, immunocytochemistry was conducted to discern the expression of Integrin β 1 and Vinculin at 12 h and 24 h. Statistical analysis was performed by the Kruskal-Wallis and Mann-Whitney U tests. Results . MTA and BD exhibited living cells up to 7 days. More expressions of Integrin β 1 and Vinculin were demonstrated in the control group, followed by BD and MTA, which also showed cellular loss and morphological changes. There was a significant difference in the experimental groups cultured for 5 and 7 days compared with the control, but there was no significant statistical difference between both cements. Conclusions . Neither material was cytotoxic during the time evaluated. There was an increase of cell adhesion through the expression of focal contacts observed in the case of BD, followed by MTA, but not significantly.